Security of Energy Supply: Comparing Scenarios From a European Perspective - Giorgio Vicini; Francesco Gracceva; Anil Markandya; Valeria Costantini (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper compares different results from a set of energy scenarios produced by international energy experts, in order to analyze projections on increasing European external energy dependence and vulnerability. Comparison among different scenarios constitutes the basis of a critical review of existing energy security policies, suggesting alternative or complementary future actions. According to the analysis, the main risks and negative impacts in the long term could be the increasing risk of collusion among exporters due to growing dependence of industrialized countries and insufficient diversification; and a risk of demand/supply imbalance, with consequent instability for exporting regions due to insufficient demand, and lack of infrastructures due to insufficient supply. Cooperation with exporting countries enhancing investments in production capacity, and with developing countries in order to reinforce negotiation capacity of energy importing countries seem to be the most effective policies at international level.
Keywords: Q40; Q41; Q48; 330; Energy security; Energy scenarios; Oil and natural gas markets; Energieversorgung; Mineralölmarkt; Erdgasmarkt; OECD-Staaten; Welt